(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Nonalcoholic Fatty Liver Disease (NAFLD) is the condition where fat accumulates in liver without significant ingestion of alcohol. NAFLD has become one of the most common liver conditions throughout the world. At the dawn of the history of NAFLD it was thought that NAFLD is disease of obese individual but lean patients are increasingly detected to have NAFLD. It seems that insulin resistance is central to the pathogenesis of NAFLD. In addition, oxidative stress and cytokines are important contributing factors, resulting in steatosis and progressive liver damage in genetically susceptible individuals. NAFLD varies considerably by ethnic group and Bangladeshi ethnicity is an independent risk factor for NAFLD. Prevalence of NAFLD in general population of Bangladesh is 4 - 18.4 %, which jumps up to 49.8% in diabetic patients. With the changes in socioeconomic condition and life style, aetiology of chronic liver disease is drifting from infectious to noninfectious diseases and the contribution of NAFLD is progressively increasing. Hepatitis B and hepatitis C have been the leading causes of mortality and morbidity from chronic liver disease in Bangladesh. But with increase in awareness and mass vaccination against HBV, prevalence of both the diseases has been decreasing in the country. The most alarming feature is that there is a high prevalence of NASH among the NAFLD patients. NAFLD is emerging as the largest contributor of chronic liver disease in Bangladesh. This warrants the attention of health policy makers and clinicians to explore this frontier and combat it from right now. J Bangladesh Coll Phys Surg 2017; 35(4): 184-191